Discourse Analysis of a Song Lyric Entitled "We Will Not Go Down” - Faizal Risdianto (Register Journal, 2016)
This library research aimed at finding the three aspect of discourse analysis: contextual, grammatical and lexical aspect of Michael Heart’s song lyrics entitled “We will not go down (Song for Gaza). After analysis it can be found that the life experience and background of the song writer and singer is closely related to the idea proposes within the song lyrics. Whereas, the result of the grammatical and lexical analysis gives a depiction of cohesion and coherence of the song discourse of “We will not Go Down (Song for Gaza)”. There are eight (8) forms of first plural personal pronoun of “We”, four (4) second plural personal pronoun of ‘You” and seven (7) third personal pronouns in various forms. On the other side, it is difficult to find lexical aspects of this song discourse. There is only one form of anaphoric repetition. The repetition of the sentence “We Will Not Go Down” seven times is to influence the hearers whether they are supporters or opponents of the idea brought by the singer/the author that whatever happens Palestinian people will not surrender to every force, nation or people that want to colonialize them.